Colliding Forms in Postapocalyptic Novels of Migration - Adinolfi, Simona (Cahier voor Literatuurwetenschap, 2024)
In this paper, I offer a comparison between the forms of migration fiction and postapocalyptic fiction. I argue that the form of “binary time” (Kaup 2021) typical of postapocalyptic narratives and that of the loop are both to be found in migration narratives too, where the narration moves back and forth to the time before and after the journey to the new country. This correspondence can be observed through Ling Ma’s 2018 work Severance. The novel foregrounds loop and binary time also by showcasing the intergenerational dialogue at play between the protagonist and her parents who migrated from China to the United States, between the young survivors and the older leader in the post-pandemic world that Severance stages. Loops and binary time are only disrupted through its ending in which the novel envisions new futurities to navigate the uncertainties that migrating in our present time entails.